THE ANALYSIS OF FISHING EFFORT BY SCRAPING NET IN SUNGAI NYAMUK, SINABOI SUB DISTRICT, ROKAN HILIR REGENCY OF RIAU PROVINCE - Fitriani '; Eni Yulinda; Hamdi Hamid (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
Research on the analysis of fishing effort by fishing scraping net, held in April2015 in Sungai Nyamuk, Sinaboi Sub District, Rokan Hilir Regency Of Riau Province.The research of aims to analyze large venture capital investments, and how large grossincome and net income of using fishing scraping net. The method used is a surveymethod. Determination respondents stratification of random sampling performed usinga method that is done by looking at the motor boat scraping levels at the study siteconsisting of a motor boat with a cargo scraping net 0,7 GT and GT 1. Respondentswere drawn consists of a fishing effort using the tool catches scraping net to charge 1GT by 3 fishermen and fishermen scraping net 0,7 GT by 3 people.The total investments invested in doing scraping net fishermen fishing effort is Rp29.647.000, for a motor boat fishermen 0,7 GT and Rp 44.295.000 for boat motors 1GT. Gross income of scraping net fishermen for season of motor boat 0,7 GT Rp.305.000 of day and Rp. 109.000 for not season of day. For motor boat 1 GT Rp.385.000 for season of day and Rp. 183.000. Net income scraping net fishermen of 0,7GT Rp. 196.000 for season of day and not net income for not season of day. As forfishermen of motor boat 1 GT is Rp. 220.000 for season of day and Rp. 18.000 for notseason of day.Keywords: Scraping Net, worthiness of business investment, Rokan Hilir